1. (a) Solve quadratic equations by completing the square. \( \begin{array}{ll}\text { (i) } 10=3 x-x^{2} & \text { (ii) } 4 x^{2}-x=8\end{array} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To solve the equation \(10 = 3x - x^2\), first rearrange it into standard form: \(x^2 - 3x + 10 = 0\). Then, complete the square: 1. Move 10 to the other side: \(x^2 - 3x = -10\). 2. Take half of -3 (\(-\frac{3}{2}\)), square it (\(\frac{9}{4}\)), and add it to both sides: \(x^2 - 3x + \frac{9}{4} = -10 + \frac{9}{4}\). 3. Simplify the right side: \(-10\) is \(-\frac{40}{4}\), so \(-\frac{40}{4} + \frac{9}{4} = -\frac{31}{4}\). 4. Now you have: \((x - \frac{3}{2})^2 = -\frac{31}{4}\). This means there are no real solutions, only complex ones! For the equation \(4x^2 - x = 8\), rearranging gives us \(4x^2 - x - 8 = 0\). Now we can complete the square: 1. Divide the entire equation by 4: \(x^2 - \frac{1}{4}x - 2 = 0\). 2. Move -2 to the other side: \(x^2 - \frac{1}{4}x = 2\). 3. Take half of \(-\frac{1}{4}\) (\(-\frac{1}{8}\)), square it (\(\frac{1}{64}\)), and add to both sides: \(x^2 - \frac{1}{4}x + \frac{1}{64} = 2 + \frac{1}{64}\). 4. The left becomes: \((x - \frac{1}{8})^2\). 5. Simplify right side: \(2\) is \(\frac{128}{64}\), so \(\frac{128}{64} + \frac{1}{64} = \frac{129}{64}\). 6. Thus, \((x - \frac{1}{8})^2 = \frac{129}{64}\). Taking the square root gives \(x - \frac{1}{8} = \pm \frac{\sqrt{129}}{8}\). So, \(x = \frac{1 \pm \sqrt{129}}{8}\). And there you have it—solutions via completing the square!